2014
DOI: 10.1159/000368930
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin, a Carotenoid Derived from Saffron (<b><i>Crocus sativus</i></b> L.), Improves Acetylcholine-Induced Vascular Relaxation in Hypertension

Abstract: Background: Hypertension is associated with endothelial dysfunction characterized by decreased vasorelaxation. Crocetin, a bioactive compound of saffron, exhibits favorable cardiovascular properties. We analyze the vasomodulatory effects of crocetin in hypertension. Methods: Myographical experiments were performed to compare the relaxation induced by acetylcholine (ACH) on aortic rings from normotensive (Wistar) and hypertensive (SHR) rats, incubated with or without crocetin or saffron extract and L Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…Crocetin has also been administrated to healthy adult human volunteers, demonstrating that it is beneficial also in humans [ 71 , 72 ]. Although only one paper reported the prevention by crocetin of CPM side effects on the bladder and liver [ 73 ], a plethora of publications reveals that crocetin can provide protection against OS induced by toxicants or underlying disorders in numerous organs, tissues, and cells [ 49 52 , 74 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crocetin has also been administrated to healthy adult human volunteers, demonstrating that it is beneficial also in humans [ 71 , 72 ]. Although only one paper reported the prevention by crocetin of CPM side effects on the bladder and liver [ 73 ], a plethora of publications reveals that crocetin can provide protection against OS induced by toxicants or underlying disorders in numerous organs, tissues, and cells [ 49 52 , 74 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…HN001, isolated from a fresh branch of the mangrove plant Sonneratia ovata , had led to the isolation and characterization of four new polyketides: nectriacid A ( 1 ), nectriacid B ( 2 ), nectriacid C ( 3 ), and 12-epicitreoisocoumarinol ( 4 ), as well as three known compounds: citreoisocoumarinol ( 5 ), citreoisocoumarin ( 6 ), and macrocarpon C ( 7 ) ( Figure 1 ). Previous studies showed that linear polyene derivatives exhibited anti-inflammatory [ 13 ], antihypertensive [ 14 ], antibacterial [ 15 ], and antifungal activities [ 16 ]. In this report, compounds ( 1 – 7 ) from the Nectria sp.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are other reports on the antihypertensive effects of other active ingredients and extracts of Crocus sativus (41)(42)(43). Some of these studies examined possible acute antihypertensive effects of CRO and crocetin (40,42,43). In this context, Shafei et al (40) showed that CRO 50, 100 and 200 mg/kg attenuated MAP, SBP and HR induced by angiotensin II.…”
Section: Discussionmentioning
confidence: 99%